2007
DOI: 10.1111/j.1460-9568.2007.05518.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional and phenotype heterogeneity of cellular prion proteins in the human brain

Abstract: Transmissible spongiform encephalopathies (TSEs) are neurological disorders that include genetic, infectious and sporadic forms of human Creutzfeldt-Jakob disease (CJD). The pathogenic agent is the prion protein that is composed of an abnormal isoform (PrP(Sc)) of a host-encoded protein (PrP(C)). Analysis of the relative amounts of PrP(Sc) glycoforms has been used to discriminate between various agents involved in TSE. The distribution and efficiency of conversion to PrP(Sc) can be influenced by differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Differential PrP C glycosylation has been documented in cell lines of different origins, but also in different organs, interestingly, depending on brain regions in mouse and human species [18,19,35,36]. Here we showed that an heterogeneity of PrP C glycopatterns was associated to bioaminergic differentiation programs.…”
Section: Discussionmentioning
confidence: 74%
“…Differential PrP C glycosylation has been documented in cell lines of different origins, but also in different organs, interestingly, depending on brain regions in mouse and human species [18,19,35,36]. Here we showed that an heterogeneity of PrP C glycopatterns was associated to bioaminergic differentiation programs.…”
Section: Discussionmentioning
confidence: 74%
“…One explanation may be that c-cleavage does not occur in cells of the brain region we sampled from, as cleavage profiles have been shown to vary in different tissues and regions [69]. Alternatively, C3 may be below the limits of detection by PAGE and western blotting.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the biological or physiological significance of PrP C proteolytic processing has not been entirely elucidated, with emerging, but sometimes conflicting evidence of separate functions of the full length [14,64,65], and different truncated PrP C species [6,10,[66][67][68]. Importantly, there are often more truncated PrP C species than full-length PrP C present in cells and tissues [33,35,69], underscoring the likely cellular requirement for these processes to occur. Through the utilization of Myc-tagged PrP C expressed in cells we discovered a novel, approximately 6-7 kDa, Myc-tagged 'C3' fragment, and then confirmed the presence of endogenous C3 in both human and animal brain tissue, indicating the fragment was not produced as an Extensive literature searching has found that the most commonly utilized antiPrP antibodies are directed to epitopes in the middle region of PrP C , and unlikely to be within the C3 fragment.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct patterns of sialylation have also been described for PrP C from either brain or spleen (Baskakov and Katorcha, 2016), and possible roles of sialylation upon functional properties of PrP C were discussed (Baskakov and Katorcha, 2016). Other studies indicated that posttranslational modifications produce a collection of differing glycosylated forms of PrP C (Pan et al, 2002), which vary across distinct brain regions (Kuczius et al, 2007b) and change with aging (Goh et al, 2007). Heterogeneous glycosylation is likely to impart selectivity of ligand binding, as suggested both by differential binding to antibodies (Li et al, 2001; Kuczius et al, 2007a) and metal ions (Moudjou et al, 2007), as well as by the differing outcomes of peripheral inoculation of TSE upon experimental prion disease in mice expressing distinct glycosylated forms of PrP C (Cancellotti et al, 2010).…”
Section: The Prion Protein As a Cell Surface Scaffold Proteinmentioning
confidence: 99%